The surveillance and assessment of acute injuries in different age categories in national wrestling championships - Can, S.; Demirkan, E.; Arici, M.; Tosun, M., I.; Cicioglu, H., I. (Chinese Journal of Traumatology, 2024)
Purpose The purpose of this study is to surveil the injuries in wrestling according to the different age categories and wrestling styles throughout the competition season.